Technologies and innovations for production system in agriculture: National policy provisions and implementation in Nepal - Timsina, Krishna; Gauchan, Devendra; Tripathi, Shreeya; Basi, Sabin; Adhikari, Surya Prasad (Nepal Public Policy Review, 2024)
Nepal’s Agriculture has rapidly embraced the concept of development and assessment since the 1960s. However, the intricacies of the sector present an ongoing challenge in identifying the necessary policy actions to foster the evolution of agricultural innovation and technologies. This study aims to review policy provisions concerning agrarian technologies and innovations that stimulate the production system. Additionally, it identifies issues and gaps, formulating potential policy solutions. The research followed a comprehensive three-step process: firstly, listing and reviewing 54 agricultural policies, and 32 acts of Nepal using a set of thirteen indicators. After that, an assessment of implementation status was done. Then consultation and validation of findings were conducted with the experts in the workshops. The findings contribute to a better understanding of policy implementation and the promotion of sustainable agricultural practices. The study found that while many policies aimed to improve agricultural production and productivity, they lacked actual measures to support increased production, such as assisting with essential inputs like labour, capital, and complementary materials. Additionally, it revealed that approximately 9% of agricultural acts and 54% of policies included provisions for production and management system technologies and innovations. However, no policy provisions for developing production technologies were found for “source seed production” and “to conserve and utilize local resources”. The study identifies that the current resource allocations for innovative production systems and management technologies are inadequate, particularly in areas like climate change, food safety, nutrition, conservation, biotechnology, and mechanization.